2015
DOI: 10.1542/peds.2015-0491
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Hemoglobin Levels and Early Cognitive and Motor Functions of One-Year-Old Children

Abstract: OBJECTIVE: To explore the relationship between prenatal hemoglobin (Hb) concentration and infant cognitive and motor functions.METHODS: Our prospective cohort study included 1-year-old children born to women enrolled at their first antenatal care (ANC) visit in Allada, Benin, before 29 weeks of pregnancy, within a trial comparing the efficacy of sulfadoxine-pyrimethamine and mefloquine. Hb concentrations of pregnant women were determined from venous blood samples collected at first and second ANC visits of at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
46
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(53 citation statements)
references
References 26 publications
3
46
4
Order By: Relevance
“…The relationship between prenatal Hb concentration and infant cognitive and motor development in our study population has already been reported in an earlier publication. 13 Considering the vulnerability of the fetus to prenatal insults and the essential role of iron in neurodevelopment, it is surprising that we found no association between prenatal ID and infant cognitive development. However, during pregnancy, the fetus has priority to iron supply over the pregnant woman's needs to ensure adequate iron stores within the first 6 months of life and 4…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…The relationship between prenatal Hb concentration and infant cognitive and motor development in our study population has already been reported in an earlier publication. 13 Considering the vulnerability of the fetus to prenatal insults and the essential role of iron in neurodevelopment, it is surprising that we found no association between prenatal ID and infant cognitive development. However, during pregnancy, the fetus has priority to iron supply over the pregnant woman's needs to ensure adequate iron stores within the first 6 months of life and 4…”
Section: Discussionmentioning
confidence: 73%
“…13 This article is therefore a secondary analysis of that data. The mothers had all been enrolled earlier in the Malaria in Pregnancy Preventive Alternative Drugs (MiPPAD) clinical trial (NCT00811421) that compared the efficacy of mefloquine and sulfadoxine pyrimethamine as intermittent preventive treatment of pregnant women (IPTp).…”
Section: Study Design and Populationmentioning
confidence: 99%
“…Accordingly, some previous studies have evidenced a relationship between suboptimal maternal diet in pregnancy and poorer mental and psychomotor development in offspring [5,6,[12][13][14][15][16]. More specifically, several studies have reported that iron deficiency (ID) in pregnancy may adversely influence brain development and be associated with infant and child behavioral problems and poorer cognitive development [5,6,13,[17][18][19][20][21]. More recently, it has been suggested that ID during pregnancy may not only have effects in early life [5,6,[21][22][23][24] but could also be related to long-term alterations in cognitive, behavior, and social development and poorer school performance during childhood and adolescence [3,12,[25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…This consequently increases the incidence of placenta previa and preterm placenta abruption. Mireku et al report a link between mothers who had anemia lower than 9.0 g/dl during pregnancy with a lower cognitive and motor development in one-year-old children [ 6 ].…”
Section: Introductionmentioning
confidence: 99%